ANALISIS KEPATUHAN LAZ SIDOGIRI DALAM MENGIMPLEMENTASIKAN PSAK 109 - Lestari, Sari; Anggraini, Arianti Dwi; Caryadi (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Amil Zakat Organization is an organization established by the government and community organizations. It has a forum function to collect and distribute zakat funds, information / alms collected. This study aims to determine whether Lazsidogiri Zakat Organization applies PSAK No. 109 in its financial statements. The proclamation of PSAK No. 109 aims to regulate the recognition, measurement, presentation in zakat, infaq / alms transactions. This type of research is a case study on Amil Zakat institutions in Sidogiri. This research uses quantitative methods combined with comparative analysis, namely comparing the financial statements prepared by LAZ Sidogiri in 2022 with PSAK 109 regulations. The data used are secondary data in the form of financial statements prepared by LAZ Sidogiri from December 2022.